Multilocus genetic models of handedness closely resemble single‐locus models in explaining family data and are compatible with genome‐wide association studies. (30th April 2013) - McManus, I. C.; Davison, Angus; Armour, John A. L.
<x xml:space="preserve">Abstract</x> Right‐ and left‐handedness run in families, show greater concordance in monozygotic than dizygotic twins, and are well described by single‐locus Mendelian models. Here we summarize a large genome‐wide association study (GWAS) that finds no significant associations with handedness and is consistent with a meta‐analysis of GWASs. The GWAS had 99% power to detect a single locus using the conventional criterion of P < 5 × 10−8 for the single locus models of McManus and Annett. The strong conclusion is that handedness is not controlled by a single genetic locus. A consideration of the genetic architecture of height, primary ciliary dyskinesia, and intelligence suggests that handedness inheritance can be explained by a multilocus variant of the McManus DC model, classical effects on family and twins being barely distinguishable from the single locus model. Based on the ENGAGE meta‐analysis of GWASs, we estimate at least 40 loci are involved in determining handedness.